2017
DOI: 10.1111/joa.12685
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional proteomic analyses of osteocytes from Xenopus laevis tested under mechanical stress conditions: preliminary observations on an appropriate new animal model

Abstract: Hitherto, the role of the osteocyte as transducer of mechanical stimuli into biological signals is far from settled. In this study, we used an appropriate model represented by the cortex of Xenopus laevis long bone diaphysis lacking (unlike the mammalian one) of vascular structures and containing only osteocytes inside the bone matrix. These structural features allow any change of protein profile that might be observed upon different experimental conditions, such as bone adaptation to stress/mechanical loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…As proposed by many authors (R. A. Dodds et al, 1993;Marotti and Palumbo, 2007;Skerry et al, 1989a,b) and largely demonstrated by Bonewald (2011) and Nakashima (Nakashima et al, 2011) osteocytes are considered the mechanosensors of bone (Bertacchini et al, 2017;Maycas et al, 2015;Nakashima et al, 2012) and are actively involved in orchestrating the function of both bone-forming osteoblasts and bone-resorbing osteoclasts. However, the role of osteocytes in osteoblast regulation, under both physiologic and pathologic conditions, is not fully characterized.…”
Section: Introductionmentioning
confidence: 97%
“…As proposed by many authors (R. A. Dodds et al, 1993;Marotti and Palumbo, 2007;Skerry et al, 1989a,b) and largely demonstrated by Bonewald (2011) and Nakashima (Nakashima et al, 2011) osteocytes are considered the mechanosensors of bone (Bertacchini et al, 2017;Maycas et al, 2015;Nakashima et al, 2012) and are actively involved in orchestrating the function of both bone-forming osteoblasts and bone-resorbing osteoclasts. However, the role of osteocytes in osteoblast regulation, under both physiologic and pathologic conditions, is not fully characterized.…”
Section: Introductionmentioning
confidence: 97%
“…This porous network allows for the transport of interstitial fluid from the vascular canals to the cells. Within this porous network, the cells are surrounded by a glycoproteic pericellular matrix less than 100 nm in thickness (PCM) (You et al, 2004), mainly made of perlecan (Thompson et al, 2011), and are attached to the wall of the lacuna through tethering perlecan fibers (Bertacchini et al, 2017;McNamara et al, 2009) with an average spacing of 40 nm (You et al, 2004). This leaves a space, the pericellular space, between the PCM and the lacunar wall, where interstitial fluids can flow from the vascular canals to the osteocytes.…”
Section: How Does the Osteocyte Sense A Mechanical Signal?mentioning
confidence: 99%
“…As regards the transmission of mechanical signals, both recent and less recent literature indicates the osteocyte as the main strain-sensitive bone cell [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. We have shown [ 42 , 43 ] that shear stress-activated osteocytes are capable of steadily increasing and maintaining the basal current produced by the ionic fluxes (streaming potentials), which occur inside the lacuno-canalicular microcavities in response to pulsing mechanical loading ( Figure 8 ).…”
Section: Osteocyte Network and Communicationsmentioning
confidence: 99%
“…Recently [ 58 ], as far as the bone adaptation-related cell-signaling is concerned, both Erk1/2 and Akt were showed to be hyperphosphorylated in frog long bones of stressed samples (forced swimming) suggesting that among the putative osteocyte signal transduction mechanisms, Akt signaling is boosted by increased mechanical stresses. Moreover, the authors confirmed again that the increase of osteocyte gap junction number is dependent on mechanical loading ( Figure 10 ).…”
Section: Osteocytes As Bone Mechanical Sensors and Transducers Of Mechanical Strains Into Biological Signalsmentioning
confidence: 99%